IMPLEMENTATION OF THE SP4N-LAPOR PROGRAM IN RESPONDING TO REPORTS AND COMMUNITY ASPIRATIONS AT THE COMMUNICATION AND INFORMATICS OFFICE OF SIMALUNGUN REGENCY - Joel F Sidabutar; Tunggul Sihombing (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
This study aims to analyze the implementation of the National Public Service Complaint Management System (SP4N-LAPOR) in responding to public reports and aspirations at the Department of Communication and Informatics (Diskominfo) of Simalungun Regency. SP4N-LAPOR is a technology-based public service innovation designed to improve transparency, accountability, and citizen participation in government administration. However, its implementation at the regional level still encounters several challenges that affect the effectiveness of complaint management. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with two SP4N-LAPOR liaison officers and two community members who had submitted complaints, supported by direct observation and documentation. The analysis was conducted using George C. Edward III’s policy implementation framework, which focuses on communication, resources, disposition, and bureaucratic structure. The findings reveal that communication among liaison officers, regional government agencies, and the public remains ineffective due to limited socialization and unclear information delivery. Resource constraints include technical disruptions, inadequate infrastructure, and the absence of dedicated budgets and incentives for implementers. In terms of disposition, weak coordination and inconsistent follow-up have reduced the effectiveness of complaint resolution, leading to public dissatisfaction. Furthermore, frequent staff rotations and the lack of a formally approved Standard Operating Procedure have created inconsistencies in implementation. The study concludes that optimizing SP4N-LAPOR requires stronger communication strategies, improved human and technical resources, accelerated institutionalization of operational procedures, and enhanced inter-agency coordination. These measures are essential to strengthen responsive, participatory, transparent, and accountable public service delivery in Simalungun Regency.